Estudio de prefactibilidad para la creación de un complejo ecoturístico en la comunidad Zaragosin parroquia Juan Montalvo del cantón Latacunga – provincia de Cotopaxi - Jordán Mosquera, Rubén Darío (2013)
To achieve the project about the creation of an ecotourism resort, it was estimated necessary to fulfill a series of processes; it was achieved starting from a main idea in an innovative scope with reference tostudy the site and to the identified necessities from a personal reference factor. In Latacunga, there is not a ecotourism resort which helps to stimulate correctly the interest of the demandanst for the environment, the culture, traditions and customs of the place for that, it is a commitment with this project to offer a new innovative, competive and total different idea. The diagnostic served as practical base in the identifications of the intrinsic and strategic characteristics of the place to follow with the researching. In the market study, the researcher made aquality analysis toidentify the correct touristic and preferred services like: interpretative walking, riding, visiting a botany garden, fishing, canopying and paintball, swimming, relaxing activities….